Live imaging reveals spatial separation of parental chromatin until the four-cell stage in Caenorhabditis elegans embryos - Bolková, Jitka; Lanctôt, Christian (The International journal of developmental biology, 2016)
The parental genomes are initially spatially separated in each pronucleus after fertilization. Here we have used green-to-red photoconversion of Dendra2-H2B-labeled pronuclei to distinguish maternal and paternal chromatin domains and to track their spatial distribution in living Caenorhabditis elegans embryos starting shortly after fertilization. Intermingling of the parental chromatin did not occur until after the division of the AB and P1 blastomeres, at the 4-cell stage. Unexpectedly, we observed that the intermingling of chromatin did not take place during mitosis or during chromatin decondensation, but rather ∼ 3-5 minutes into the cell cycle. Furthermore, unlike what has been observed in mammalian cells, the relative spatial positioning of chromatin domains remained largely unchanged during prometaphase in the early C. elegans embryo. Live imaging of photoconverted chromatin also allowed us to detect a reproducible 180° rotation of the nuclei during cytokinesis of the one-cell embryo. Imaging of fluorescently-labeled P granules and polar bodies showed that the entire embryo rotates during the first cell division. To our knowledge, we report here the first live observation of the initial separation and subsequent mixing of parental chromatin domains during embryogenesis.
Keywords: blastomery; Animals; Luminescent Proteins; Fertilization; Female; fertilizace; ženské pohlaví; Cell Cycle; embryo nesavčí; Chromatin; Caenorhabditis elegans; Time Factors; časové faktory; Time-Lapse Imaging; Blastomeres; Mitosis; buněčný cyklus; mitóza; Male; luminescentní proteiny; časosběrné zobrazování; chromatin; Embryo, Nonmammalian; histony; Histones; zvířata; mužské pohlaví